2020
DOI: 10.1038/s41598-020-78598-3
|View full text |Cite|
|
Sign up to set email alerts
|

Growth of sillenite Bi12FeO20 single crystals: structural, thermal, optical, photocatalytic features and first principle calculations

Abstract: Ideal sillenite type Bi12FeO20 (BFO) micron sized single crystals have been successfully grown via inexpensive hydrothermal method. The refined single crystal X-ray diffraction data reveals cubic Bi12FeO20 structure with single crystal parameters. Occurrence of rare Fe4+ state is identified via X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS). The lattice parameter (a) and corresponding molar volume (Vm) of Bi12FeO20 have been measured in the temperature range of 30–700 °C by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The XPS peaks at a binding energy of 710 and 723.5 eV indicate the presence of Fe 3+ 2p 3/2 and Fe 3+ 2p 1/2 orbitals, whereas 712 and 725.6 eV indicate the presence of Fe 4+ 2p 3/2 and Fe 4+ 2p 1/2 orbitals demonstrating the presence of Fe 3+ and Fe 4+ oxidation states. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS peaks at a binding energy of 710 and 723.5 eV indicate the presence of Fe 3+ 2p 3/2 and Fe 3+ 2p 1/2 orbitals, whereas 712 and 725.6 eV indicate the presence of Fe 4+ 2p 3/2 and Fe 4+ 2p 1/2 orbitals demonstrating the presence of Fe 3+ and Fe 4+ oxidation states. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The XPS peaks at a binding energy of 710 and 723.5 eV indicate the presence of Fe 3+ 2p 3/2 and Fe 3+ 2p 1/2 orbitals, whereas 712 and 725.6 eV indicate the presence of Fe 4+ 2p 3/2 and Fe 4+ 2p 1/2 orbitals demonstrating the presence of Fe 3+ and Fe 4+ oxidation states. [32,33] Based on the in situ and ex situ analyses, it is convincible that the mixed-phase NFMO-P2/O3 cathode could deliver an outstanding electrochemical performance compared with that of the other single-phase ternary mixtures of Na 1−x NFMO cathodes. The preliminary electrochemical performance of the NFMO-P2/O3 cathode was evaluated using cyclic voltammetry (CV) in a wide voltage range of 1.5-4.5 V versus Na/Na + at a scan rate of 0.1 mV s -1 as represented in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, among all the samples tabulated here, S-BFO(160) showed the highest efficiency with almost complete degradation of RhB and MB dye within 120 and 180 min of solar irradiation. Moreover, most studies presented here on photocatalytic performance of sillenite BFO samples evaluated the photocatalytic activity of the photocatalyst by the degradation of colored dye alone, which is known to sensitize a photocatalytic reaction. , However, in our experiment, along with colored dyes, we have examined the photocatalytic properties of our synthesized samples through the degradation of colorless antibiotic, which indicated that the degradation is purely photocatalytic, not dye-sensitized. , Though in most of the earlier studies, the sillenite BFO samples were synthesized following a facile solvothermal or hydrothermal reaction route, the process was very time-consuming, and the photocatalytic activity was not very promising. , However, in the present investigation, we were able to produce sillenite-structured BFO within 6 h at a very lower reaction temperature of 140–160 °C without any sort of pre/post-processing time and energy consuming steps. Moreover, in earlier investigations on the photocatalytic performance of both sillenite- and perovskite-phase BFO, the presence of H 2 O 2 in the reaction medium has been observed to facilitate the pollutant degradation rate, which is not preferable from the eco-friendly point of view. , However, in the present investigation, we have observed very good pollutant deterioration efficiency of our synthesized photocatalyst without introducing any toxic reagent in the reaction medium.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, most studies presented here on photocatalytic performance of sillenite BFO samples evaluated the photocatalytic activity of the photocatalyst by the degradation of colored dye alone, which is known to sensitize a photocatalytic reaction. 51,52 However, in our experiment, along with colored dyes, we have examined the photocatalytic properties of our synthesized samples through the degradation of colorless antibiotic, which indicated that the degradation is purely photocatalytic, not dye-sensitized. 11,48 Though in most of the earlier studies, the sillenite BFO samples were synthesized following a facile solvothermal or hydrothermal reaction route, the process was very time-consuming, and the photocatalytic activity was not very promising.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Their overall structure is described by the atom of bismuth surrounded by seven oxygen atoms that share corners with other similar Bi polyhedrons and with MO4 which represents a tetravalent ion or a combination of ions that exist both at the cube center and on the corners in the BMO structure [23,24]. There are a significant number of new sillenites that are used as photo-catalysts in previous research, such as Bi12TiO20 [25], Bi12GeO20 [21], Bi12PbO19 [22], Bi12CoO20 [26], Bi12SiO20 [21], Bi12MnO20 [17], Bi12FeO20 [27] and Bi12ZnO20 [28]. Among the sillenite crystals, bismuth nickelate Bi12NiO19 (BNO) has not been used as a photocatalyst yet, although it has recently gained considerable attention because of its tiny bandgap, its high photoconductivity, ease of separation of photogenerated electron-hole pairs and ease of recycling [29][30][31].…”
Section: Introductionmentioning
confidence: 99%